Nocturnal hypoxaemia and quality of sleep in patients with chronic obstructive lung disease. Issue 11 (November 1986) - Cormick, W; Olson, L G; Hensley, M J; Saunders, N A
Abstract : Fifty patients with chronic obstructive lung disease were questioned about their sleep quality and their responses were compared with those of 40 similarly aged patients without symptomatic lung disease. Patients with chronic obstructive lung disease reported more difficulty in getting to sleep and staying asleep and more daytime sleepiness than the control group. More than twice as many patients (28%) as controls (10%) reported regular use of hypnotics. In a subgroup of 16 patients with chronic obstructive lung disease (mean FEV1 0.88 (SD 0.44) sleep, breathing, and oxygenation were measured to examine the relationship between night time hypoxaemia and sleep quality. Sleep architecture was disturbed in most patients, arousals occurring from three to 46 times an hour (mean 15 (SD 14)/h). Arterial hypoxaemia during sleep was common and frequently severe. The mean (SD) arterial oxygen saturation (SaO2) at the onset of sleep was 91% (7%). Nine patients spent at least 40% of cumulative sleeping time at an SaO2 of less than 90% and six of these patients spent 90% of sleeping time below this level. Only four of 15 patients did not develop arterial desaturation during sleep. The mean minimum SaO2 during episodes of desaturation was less in rapid eye movement (REM) sleep (72% (17%)) than in non-REM sleep (78% (10%), p less than 0.05). The predominant breathing abnormality associated with desaturation was hypoventilation; only one patient had obstructive sleep apnoea. Arousals were related to oxygenation during sleep such that the poorer a patient's arterial oxygenation throughout the night the more disturbed his sleep (arousals/h v SaO2 at or below which 40% of the total sleep time was spent: r = 0.71, p less than 0.01). Hypoxaemia during sleep was related to waking values of SaO2 and PaCO2 but not to other daytime measures of lung function.